Click consonants in contact: a comparative sociohistorical analysis with special reference to Nama-Afrikaans contact - Christie, Camilla Rose (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Language Studies)
Despite their ubiquity across southern Africa, click consonants are among the world's most poorly understood speech sounds. Details of their phonological behaviour during language contact remain unclear, in large part because of the under-documentation of contact events of marginalised languages in rural contexts. Working within a sociohistorical linguistic framework with reference to material socioeconomic theories of language contact, this thesis compares and contrasts the diachronic phonological outcomes of various click loan events. The primary event under investigation is the donation of loanwords from an endangered click language, Nama, via substrate interference with the lexicon of a socially dominant clickless language, Afrikaans, in the Namaqualand region of the Northern Cape. The phonological adaptations employed to integrate donated lexical material into a host grammar ought ordinarily to be fairly regular, but the cross-linguistic rarity of click consonants complicates this process. The twenty click consonants expected of Nama undergo phonemic neutralisation when realised in Namaqualand Afrikaans, such that contrast embedded in click 'type' and click 'accompaniment' is collapsed. Speakers of Namaqualand Afrikaans employ any click type when uttering any click word, and may even use different click types in different tokens of the same lexical item. This unpredictability neutralises contrast. Nonetheless, there is some evidence of a diachronic trend from the unpredictable use of multiple click types and accompaniments toward the stable use of only the linguopulmonic dental click. When these novel data are set against the phonological outcomes of other contact events between a click language and a clickless languages across southern Africa, the normal outcome of click loan under is shown to be the collapse of 'type' contrasts. An important outlier is the large 'type'-contrasting click inventory still shared by isiXhosa and isiZulu long after the extinction of donor click languages in the Khoekhoe branch, suggesting that this contact event must historically have entailed sustained community-wide bilingualism. These comparative observations are used to develop a cross-linguistic typology of click loan events that aims to improve our understanding of the precolonial linguistic landscape of southern Africa. The improved documentation of click consonants in rural language varieties is urgently recommended.
Keywords: Click consonant; Language contact; Sociohistorical linguistics; Sociolinguistics; Nama language; Khoekhoe; African languages; Linguistic borrowing